2009
DOI: 10.2522/ptj.20080052
|View full text |Cite
|
Sign up to set email alerts
|

An Intensive, Progressive Exercise Program Reduces Disability and Improves Functional Performance in Patients After Single-Level Lumbar Microdiskectomy

Abstract: An intensive, progressive exercise program combined with education reduces disability and improves function in patients who have undergone a single-level lumbar microdiskectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 34 publications
(2 reference statements)
1
35
0
2
Order By: Relevance
“…90 Clinical trials demonstrating improved outcomes following postoperative rehabilitation emphasize the use of lumbar stabilization exercise, and initiate treatment sooner in the postoperative period. 9,11,16,23,66,74,77,86,113 Additionally, morphological changes of the LM and functional impairments of the LM and TrA are related to disorders of the lumbar spine. 1,13,37,41,48,50,51,57,61,63,88 Integrating these 3 issues was the impetus in the design of the rehabilitation approach used in this case report.…”
Section: Muscle Morphologymentioning
confidence: 99%
“…90 Clinical trials demonstrating improved outcomes following postoperative rehabilitation emphasize the use of lumbar stabilization exercise, and initiate treatment sooner in the postoperative period. 9,11,16,23,66,74,77,86,113 Additionally, morphological changes of the LM and functional impairments of the LM and TrA are related to disorders of the lumbar spine. 1,13,37,41,48,50,51,57,61,63,88 Integrating these 3 issues was the impetus in the design of the rehabilitation approach used in this case report.…”
Section: Muscle Morphologymentioning
confidence: 99%
“…The test began in a position that was 75° above the horizontal (level 1) and descended in 15° surgery alone. 3,7,12 A postsurgical therapy program should be comprehensive, including patient education, and exercises for the trunk and lower extremities, including the hips. 12 An emphasis should be placed on the lumbar extensors, which play a key role in spinal stability 17 and have been shown to be deficient following SLM.…”
mentioning
confidence: 99%
“…3,7,12 A postsurgical therapy program should be comprehensive, including patient education, and exercises for the trunk and lower extremities, including the hips. 12 An emphasis should be placed on the lumbar extensors, which play a key role in spinal stability 17 and have been shown to be deficient following SLM. 7 The landmark study by Beiring-Sorensen 2 determined that lumbar extensor endurance was better than maximal strength in predicting persons who would develop low back pain.…”
mentioning
confidence: 99%
“…After surgery, patients needed 29 s to perform five STSTS movements without vision, although healthy young individuals only needed 8 s (Claeys et al, 2012). Another study, with individuals with comparable moderate-to-high ODI scores after surgery, reported the need for 18 s after lumbar surgery but with vision (Kulig et al, 2009). Additionally, we found a comparable degree of down-weighting of lumbosacral proprioceptive signals and up-weighting of ankle proprioceptive signals in individuals with non-specific LBP without surgical history (Claeys et al, 2011), that affected STSTS performance (Claeys et al, 2012).…”
Section: Discussionmentioning
confidence: 99%